THE EFFECT OF DOSE PREGNANT MARE SERUM GONADOTROPIN (PMSG) HORMONE ON EGG DIAMETER AND EGG FECUNDITY OF Channa striata - Rizal Akbar Hutagalung (Journal of Aquaculture Development and Environment, 2019)
Channa striata is a fishery commodity that has high economic value. However, the availability of cork fish is very dependent on the availability of nature due to the lack of technology in the provision of seeds in a sustainable manner. In general, semi-artificial spawning with hormone induction is done for parent efficiency as well as increasing the quality and quantity of fish eggs as potential fish seeds. One of the spawning hormones that can be used is Pregnant Mare Serum Gonadotropin (PMSG), this hormone contains many elements folicle stimulating hormon (FSH) which can trigger gonad maturation in the early stages of oocyte formation and egg yolk filling in the process of vitelogenesis which will have an impact on egg diameter and fecundity. The purpose of this study is to determine the optimal dose of the PMSG hormone to increase egg quality in this case is the diameter of the egg and the quantity of eggs in this case is fecundity. The female cork fish used has a size range of 30-40 cm with a weight of 500 - 700 g, adapted in a controlled container then PMSG hormone induced by treatment A dose: 0.75 mL / kg; B: 1.0 mL / kg; C: 1.25 mL / kg; D: 1.5 mL / kg and repeated three times. Then wait up to 72 hours to find out the development of oocytes. The results showed that the best treatment for egg diameter with a dose of 1.25 mL / kg with an egg size of 1.04 mm, whereas in fecundity with a hormone dose of 1.5 mL / kg produced 23,612 eggs.